Telaah Hukum Islam Tentang LGBT (Sebuah Solusi dalam Memecahkan Problem Kemasyarakatan) - Dahlia Haliah Ma’u (PSGA LP2M IAIN Pontianak, 2016)
The Lesbian, Gay, Bisexual, and Transgender (in Indonesia known as LGBT) are fahisyah (bad/nasty) behaviors that are clearly prohibited in Islam. Those behaviors were performed by Prophet Luth people in the past and be included in Quran and Hadith. The fuqaha agreed that the behaviors are forbidden for Moslems since the negative impact to the doers and societies. Furthermore, the Islamic Law has categorized the punishmet to those who practice the behaviors. First, the doer would be killed or rajam (being thrown with stones until death). Second, the similar punishment to people who practice adultery or free sex (zina); If the doer is married (muhsan), the sanction is rajam, and if the doer is not married yet (ghairu muhsan), he/she would be whipped a hundred times. Third, the performer of those behaviors would be punished by the government or a judge (ta’zir), the level of the sanction would be decided by the government or a judge fairly. Moreover, the government, ulama, and societies have an important role to avoid these nasty behaviors through the implementation of the rules formally, and verbal persuasion.